2008
DOI: 10.1152/ajpendo.90388.2008
|View full text |Cite
|
Sign up to set email alerts
|

The facilitative glucose transporter GLUT3: 20 years of distinction

Abstract: Glucose metabolism is vital to most mammalian cells, and the passage of glucose across cell membranes is facilitated by a family of integral membrane transporter proteins, the GLUTs. There are currently 14 members of the SLC2 family of GLUTs, several of which have been the focus of this series of reviews. The subject of the present review is GLUT3, which, as implied by its name, was the third glucose transporter to be cloned (Kayano T, Fukumoto H, Eddy RL, Fan YS, Byers MG, Shows TB, Bell GI. J Biol Chem 263: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
322
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(360 citation statements)
references
References 133 publications
15
322
0
3
Order By: Relevance
“…Another immunostaining study using the rat testis described the tissue sections as showing immunoreactivities for all MCT1, MCT2, and MCT4 in interstitial cells, together with MCT1 in "surrounding spermatogenic cells in the seminiferous tubules" and with MCT2 on the tails of spermatozoa (3). More recently, Mannowetz et genesis, thus providing mature sperm with GLUT3 to utilize glucose for successful fertilization (34,38). The seminiferous tubules construct a diffusion barrier against free passage to the adluminal compartment, as confirmed by the present immunostaining of the tight junction protein, ZO-1.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Another immunostaining study using the rat testis described the tissue sections as showing immunoreactivities for all MCT1, MCT2, and MCT4 in interstitial cells, together with MCT1 in "surrounding spermatogenic cells in the seminiferous tubules" and with MCT2 on the tails of spermatozoa (3). More recently, Mannowetz et genesis, thus providing mature sperm with GLUT3 to utilize glucose for successful fertilization (34,38). The seminiferous tubules construct a diffusion barrier against free passage to the adluminal compartment, as confirmed by the present immunostaining of the tight junction protein, ZO-1.…”
Section: Resultssupporting
confidence: 66%
“…GLUT3 in rodents is present at high levels only in neuronal tissues (27). In addition to the brain, sperm abundantly express GLUT3; GLUT3 expressed along the entire length of the sperm tails enables the effective utilization of glucose and/or fructose (34). Sperm require a large amount of ATP, which is supplied primarily by glucose in the lumen of the female reproductive tract (2).…”
mentioning
confidence: 99%
“…In our model, we observed that short treatments with Wnt3a did not affect the expression or localization of the major GLUT transporter described in neurons (i.e. GLUT3) (58). However, after 30 min of treatment, we observed an increase in the affinity of the transporter for the substrate.…”
Section: Wnt Signaling Stimulates Glucose Utilization In Neuronsmentioning
confidence: 55%
“…Under physiological conditions, Glut3 is expressed predominantly in the brain tissue (2). The abnormal overexpression of Glut3 has been detected in numerous types of cancer, including breast, oral, lung, colon and bladder cancer, however, the underlying mechanism remains unclear (3)(4)(5)21).…”
Section: Discussionmentioning
confidence: 99%
“…To offset this disadvantage, the glycolytic rate in tumor cells is 100x higher than that in normal cells, and glucose uptake into tumor cells is also accelerated (1). A family of glucose transporters (Gluts) facilitates glucose movement across the plasma membranes in a tissue-specific manner, and 14 different Glut isoforms have been characterized at present (2). Glut3 is an effective glucose transporter, previous studies have demonstrated that Glut3 is upregulated in certain types of malignancy and that it is associated with poor prognosis (3,4).…”
Section: Introductionmentioning
confidence: 99%